Analisa Pengaruh Kompetensi, Independensi, Serta Fee Audit Terhadap Kualitas Audit: Studi KAP Semarang - Putriana, Nada Syifaa Bella; Hanum, Ayu Noviani; Kristiana, Ida (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2022)
This research aims to prove empirically the effect of competence, independence, and audit fees on audit quality with the object of research at the Semarang public accounting firm. the method of research using quantitative and primary data which is form of a questionnaire. The sampling of research using the convenience sampling technique, which is a technique refers to respondents who are willing to fill out a questionnaire regardless of gender, age, and length of work experience. The results of research to indicate competence and independence that have a indicatory positive impact on audit quality. Meanwhile, the Audit Fee has a positive and it is not significant with that.